Spin nano-oscillator-based wireless communication - Choi, Hyun Seok; Kang, Sun Yool; Cho, Seong Jun; Oh, Inn-Yeal; Shin, Mincheol; Park, Hyuncheol; Jang, Chaun; Min, Byoung-Chul; Kim, Sang-Il; Park, Seung-Young; Park, Chul Soon (NATURE PUBLISHING GROUP, 2014)
Spin-torque nano-oscillators (STNOs) have outstanding advantages of a high degree of compactness, high-frequency tunability, and good compatibility with the standard complementary metal-oxide-semiconductor process, which offer prospects for future wireless communication. There have as yet been no reports on wireless communication using STNOs, since the STNOs also have notable disadvantages such as lower output power and poorer spectral purity in comparison with those of LC voltage-controlled oscillators. Here we show that wireless communication is achieved by a proper choice of modulation scheme despite these drawbacks of STNOs. By adopting direct binary amplitude shift keying modulation and non-coherent demodulation, we demonstrate STNO-based wireless communication with 200-kbps data rate at a distance of 1 m between transmitter and receiver. It is shown, from the analysis of STNO noise, that the maximum data rate can be extended up to 1.48 Gbps with 1-ns turn-on time. For the fabricated STNO, the maximum data rate is 5 Mbps which is limited by the rise time measured in the total system. The result will provide a viable route to real microwave application of STNOs.